Neuroimaging correlates of blinking abnormalities in patients with progressive supranuclear palsy. Issue 1 (4th December 2015) - Bologna, Matteo; Piattella, Maria Cristina; Upadhyay, Neeraj; Formica, Alessandra; Conte, Antonella; Colosimo, Carlo; Pantano, Patrizia; Berardelli, Alfredo
Abstract: Objective: We aimed to identify the possible relationship between blinking abnormalities and neuroimaging changes in patients with progressive supranuclear palsy. Methods: We studied 18 patients with progressive supranuclear palsy and 13 healthy subjects. Voluntary and spontaneous blinking were recorded using kinematic techniques. Changes in brain structures were detected by T1‐weighted magnetic resonance imaging and voxel‐based morphometry. We then sought possible correlations between blinking and neuroimaging abnormalities in patients. Results: Kinematic analysis indicated several abnormalities during voluntary blinking and a markedly reduced spontaneous blink rate in patients compared with healthy subjects. Neuroimaging showed gray matter loss in cortical and subcortical structures and lower white matter volume in the brainstem. Gray matter loss in subcortical structures correlated with the prolonged pause duration between the closing and opening phases, during voluntary blinking. Conclusions: This study provides a more specific insight into the pathophysiological mechanisms underlying blinking abnormalities in progressive supranuclear palsy. © 2015 Movement Disorder Society